Nanodisc single-molecule pulldown to study lipid-protein interactions - Adriana Reyes-Ordoñez; Shweta Shree; Nilmani Singh; Stephen G. Sligar; Jie Chen (Journal of Lipid Research, 2025)
Beyond serving structural roles in the cell membrane, many phospholipids, including phosphatidylinositol phosphates (PIPs), are key signaling molecules that regulate a myriad of cellular processes. Specific interactions with PIPs are crucial for the functions of many signaling proteins, highlighting the need for a convenient and robust method to study lipid-protein interactions. Previously, we established a fluorescence microscopy-based lipid single-molecule pulldown (lipid-SiMPull) assay for detecting interactions between fluorescently tagged proteins of interest in whole-cell lysates and small unilamellar vesicles containing phospholipids of interest. Despite unique advantages of the lipid-SiMPull assay, small unilamellar vesicle is not an optimal membrane model due to its instability, heterogeneity in size, and a membrane curvature inconsistent with the relative flatness of the cell membrane. Here, we report the use of lipid Nanodiscs in lipid-SiMPull. Using PIP-protein pairs of known interactions, we show that Nanodiscs containing various PIPs can pull down protein targets specifically, with an estimated detection threshold of Kd in the 10–20 μM range. Remarkably, we find that each Nanodisc is bound by one copy of the protein (or protein dimer), conferring true single-molecule resolution to the assay. Transient interactions are characterized by the rebinding of proteins to individual Nanodiscs, and dissociation rates (koff) are determined from dwell time analysis. We apply this assay to interrogate structural requirements for the stability of AKT binding of PI(3,4,5)P3 and find that an intramolecular interaction between the PH domain and kinase domain is critical for stabilizing the AKT-PI(3,4,5)P3 interaction. This work estalishes the Nanodisc SiMPull assay as a simple and powerful approach for investigating protein-lipid interactions with single-molecule resolution.